Dialog Humanistik dalam Pendidikan menurut Paulo Freire - Polikarpus Raga (Unika Santu Paulus Ruteng, 2023)
This paper describes Paulo Freire's thoughts on humanistic education. The background of this study is the dehumanization situation in our society today, which is caused by unfair practices. The method used is a literature review, by collecting book sources and journal articles that talk about Freire's views on humanistic education. Historically Freire's humanistic education emerged from his struggle with the practice of injustice towards the poor. They are oppressed because of the poverty they experience. This practice resulted in dehumanization. Dehumanization can only be changed through a dialogical educational process. According to Freire, humans are naturally beings who are aware of their existence in and within the world. Because of this, humans in their practical experience are always in dialogue with the world. The oppressed are invited to recognize and be aware of the reality of the oppression they experience in this educational process, then struggle to overcome this oppressed situation. The aim of dialogic education is to regain human values that have been taken away due to acts of oppression. With that dehumanization is changed to humanization. According to Freire, the ontological need for every human being is to become a complete human being in his existence. It is the duty of education to help every human being to become a complete human being in the reality of his life. It must be admitted that our nation's society is currently experiencing a crisis in many aspects. These crises are actually rooted in the humanitarian crisis. There are many practices of injustice that sacrifice the rights of many people. Paulo Freire's humanistic educational approach can be used as a basis for facing and resolving this crisis